Tenascin-C, presepsin (sCD14-ST), and neutrophil-to-lymphocyte ratio as complementary circulating biomarkers for sepsis-associated organ dysfunction and 28-day all-cause mortality: a biomarker-enriched prognostic model: Circulating biomarkers and prognosis in sepsis - Xie, Yuxiang; Xie, Chengzhi (Journal of Medical Biochemistry, 2026)
Background: Sepsis is characterized by dysregulated host responses with subsequent organ dysfunction. Conventional biomarkers (e.g., procalcitonin) incompletely reflect tissue injury and immune activation. We evaluated the clinical laboratory value of circulating Tenascin-C (TNC), presepsin (sCD14-ST), and the neutrophil-to-lymphocyte ratio (NLR) as complementary biomarkers of organ dysfunction severity and short-term prognosis in sepsis.Methods: This retrospective observational study enrolled 103 adult ICU patients fulfilling Sepsis-3 criteria (June 2023–June 2025). Peripheral blood was collected within 12 h of ICU admission. Serum TNC was measured by ELISA; sCD14-ST was quantified by chemiluminescent enzyme immunoassay; NLR was calculated from routine blood counts. Associations with organ dysfunction were assessed using Spearman correlation with SOFA scores. Independent associations with 28-day all-cause mortality were examined using multivariable logistic regression. Predictive performance of a clinical baseline model (age, SOFA, PCT) versus a biomarker-enriched model (baseline + TNC, sCD14-ST, NLR) was evaluated by ROC analysis.Results: TNC, sCD14-ST, and NLR were higher in septic shock than sepsis and were elevated in non-survivors versus survivors (all P < 0.05). TNC showed the strongest correlation with SOFA (r = 0.466, P < 0.001), followed by sCD14-ST (r = 0.352, P < 0.001) and NLR (r = 0.299, P = 0.002). In multivariable analysis, TNC, sCD14-ST, and NLR remained independently associated with 28-day all-cause mortality. The biomarker-enriched model improved discrimination compared with the baseline model (AUC 0.928 vs. 0.867), with higher sensitivity (84.4% vs. 71.9%).Conclusions: Admission TNC, sCD14-ST, and NLR capture complementary biochemical dimensions of sepsis (tissue injury, innate immune activation, and immune imbalance) and improve risk stratification for organ dysfunction and 28-day all-cause mortality when added to routine clinical variables. These findings support a pragmatic, laboratory-based multimarker approach for early prognostic assessment in sepsis. Keywords: Tenascin-C; Presepsin (sCD14-ST); Sepsis-associated organ dysfunction; Biomarker-based risk stratification; 28-day all-cause mortality.
Keywords: Tenascin-C; Presepsin (sCD14-ST); Sepsis-associated organ dysfunction; Biomarker-based risk stratification; 28-day mortality